Curriculum co-creation as a transformative strategy to address differential student outcomes: the example of Kingston University's Student Curriculum Consultant Programme. (2019) - Hughes, Annie Livingstone; Michener, Christina; Mohamed, Kamal; McDuff, Nona
No abstract available